Adaptation to Sodium Hypochlorite and Potassium Permanganate May Lead to Their Ineffectiveness Against Candida albicans - Tomasz M. Karpiński; Marzena Korbecka-Paczkowska; Marcin Ożarowski; Donald Włodkowic; Marzena Liliana Wyganowska; Agnieszka Seremak-Mrozikiewicz; Judyta Cielecka-Piontek (Pharmaceuticals)
Background/Objectives: Adaptation can reduce or completely eliminate the effectiveness of antibiotics and antiseptics at clinical concentrations. To our knowledge, no studies have examined fungal adaptation to antiseptics. This study aimed to preliminarily investigate the potential for Candida albicans adaptation to eight antiseptics. Methods: The minimal inhibitory concentration (MIC), drug susceptibility, adaptation to antiseptics, and Karpinski Adaptation Index (KAI) of C. albicans strains were assessed. Results: The antiseptics with the most effective MICs activity against C. albicans were octenidine dihydrochloride (OCT), chlorhexidine digluconate (CHX), and polyhexamethylene biguanide (polyhexanide, PHMB). Sodium hypochlorite (NaOCl) and ethacridine lactate (ET) demonstrated moderate activity, while boric acid (BA), povidone–iodine (PVI), and potassium permanganate (KMnO4) showed the weakest activity. The MIC values for NaOCl and KMnO4 were close to or equal to the clinical concentrations used in commercial products. The studied strains were susceptible to econazole, miconazole, and voriconazole. Resistance to other drugs occurred in 10–30% of the strains. Antifungal resistance remained unchanged after antiseptic adaptation testing. The lowest KAI values, indicating very low resistance risk, were observed for CHX, OCT, and PHMB. PVI and BA presented a low risk, ET a moderate risk. KMnO4 and NaOCl had the highest KAI values, indicating high and very high resistance risk in Candida yeasts. Conclusions: C. albicans strains can adapt to antiseptics to varying extents. For most antiseptics, adaptation does not significantly affect their clinical efficacy. However, due to adaptation, NaOCl and KMnO4 may become ineffective against C. albicans strains even at clinical concentrations.